1999
DOI: 10.3354/ame017049
|View full text |Cite
|
Sign up to set email alerts
|

Responses of three freshwater planktonic ciliates with different feeding modes to cryptophyte and diatom prey

Abstract: The filter feeding oligotrich ciliate Strobilidium lacustris, the raptorial prostome ciliate Balanion planctonicu~n and the diffusion feeding scuticociliate Histiobalantium bodamicurn could be cultivated for months/years on a sole &et of Cryptomonas sp., whereas the diatom Stephanodiscus hantzschii did not support their growth. With Cryptornonas sp. as food, numerical responses of all ciliates followed a modified Michaelis-Menten model, which at lS°C yielded maximum growth rates of 0.96. 1.87 and 0.33 d-' and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 19 publications
8
74
1
Order By: Relevance
“…The numerical and functional response curves further demonstrate that M. corlissi should be highly competitive in many warm-temperate and (sub)tropical lakes. The threshold food concentration for population growth is comparable to that of other planktonic ciliate species obtained under similar food and temperature conditions (Müller & Schlegel 1999, Weisse et al 2002, but at the high end of values reported for oligotrich ciliates (Jakobsen & Hansen 1997 and references therein, Montagnes & Lessard 1999, Müller & Schlegel 1999. The threshold level corresponds to a chlorophyll a concentration of approximately 2.5 µg l -1 , assuming a carbon to chlorophyll a ratio of 40:1 (Banse 1977, Montagnes et al 1994), or to a bacterial abundance of 2 to 10 × 10 9 cells l -1…”
Section: Meseres Corlissi: a Globally Distributed But Locally Thrivinsupporting
confidence: 50%
“…The numerical and functional response curves further demonstrate that M. corlissi should be highly competitive in many warm-temperate and (sub)tropical lakes. The threshold food concentration for population growth is comparable to that of other planktonic ciliate species obtained under similar food and temperature conditions (Müller & Schlegel 1999, Weisse et al 2002, but at the high end of values reported for oligotrich ciliates (Jakobsen & Hansen 1997 and references therein, Montagnes & Lessard 1999, Müller & Schlegel 1999. The threshold level corresponds to a chlorophyll a concentration of approximately 2.5 µg l -1 , assuming a carbon to chlorophyll a ratio of 40:1 (Banse 1977, Montagnes et al 1994), or to a bacterial abundance of 2 to 10 × 10 9 cells l -1…”
Section: Meseres Corlissi: a Globally Distributed But Locally Thrivinsupporting
confidence: 50%
“…An analysis of long-term plankton data in the North Sea showed similar patterns for mesozooplankton communities as shifts in species composition and increases in diversity were observed (Beaugrand 2004;Hays et al 2005). However, Irigoien et al (2004) characterized microzooplankton diversity predominantly as a unimodal function of phytoplankton biomass, and ciliates are known to show a high species specificity regarding food concentrations, feeding preferences and temperature requirements (Mueller and Schlegel 1999;Weisse et al 2001). Thus, it can be assumed that the combined effect of temperature, food supply and food composition might be responsible for the high diversity in the warmer set-ups.…”
Section: Ciliate Community Compositionmentioning
confidence: 92%
“…The food vacuoles of, e.g., Rimostrombidium lacustris or R. humile were densely packed with centric diatoms. Müller and co-workers (Müller 1989, Müller et al 1991b, Müller & Schlegel 1999 observed that the spring assemblage of Lake Constance (mainly B. planctonicum and Rimostrombidium spp.) was closely related to food resources and able to respond rapidly to a bloom of small phytoplankton.…”
Section: Histiobalantium Bodamicummentioning
confidence: 99%
“…At this time of the year, ciliates might be strong competitors with metazoan organisms, due to low generation times; hence, ciliates like B. planctonicum were assumed to be important contributors to the beginning of the so-called clearwater phase in meso-to eutrophic lakes, in addition to rotifers and other ciliates (Sommaruga & Psenner 1993. Generally, they were among the first grazers of algal biomass in spring, with a preference for cryptophytes (Carrick & Fahnenstiel 1989, Müller et al 1991b, Müller & Schlegel 1999.…”
Section: Springmentioning
confidence: 99%